Population structures and seasons affected flowering, pollination and reproductive outputs of sandalwood in Gunung Sewu, Java, Indonesia - YENI W.N. RATNANINGRUM; SAPTO INDRIOKO; ENY FARIDAH; ATUS SYAHBUDIN (Nusantara Bioscience, 2018)
Ratnaningrum YWN, Indrioko S, Faridah E, Syahbudin A. 2018. Population structures and seasons affected flowering, pollination and reproductive outputs of sandalwood in Gunung Sewu, Java, Indonesia. Nusantara Bioscience 10: 12-26. Sandalwood was the origin to the south-eastern islands of Indonesia, but is recently occurred as new landraces in Gunung Sewu Geopark, Java, Indonesia. This study compared flowering and pollination, and their effect on reproductive outputs, among sandalwood populations in Gunung Sewu, during the dry and rainy season of 2016 flowering period. Flowering and pollination rate differed significantly between seasons but were similar among sites. Oppositely, reproductive outputs differed significantly among sites, but were similar between seasons. The rainy season produced more flowers and pollination. Pollination was less correlated to flowers abundance, but more affected by population size. The higher and cooler population visited more by Dipterans (31.8% to 32.6%) and Hymenopterans (28.2% to 30%), while the warmer, lower sites dominated by Lepidopterans (37.2% to 43%) and Dipterans (32.9% to 38.2%). Higher population received fewer visits, but more visitors diversity (28 families). In contrast, lower sites received more visits, but with less diversity (20 families). Most insect families were considered â€œRareâ€ and â€œOccasionalâ€. However, pooled altogether, the whole families of Lepidopterans and Dipterans considered â€œFrequentâ€ and â€œEffectiveâ€. The Hymenopterans considered â€œFrequentâ€ and â€œEffectiveâ€ at Nglanggeran and Wanagama. The Cicadellidae of Coleopterans, along with arachnids and grasshoppers, were considered robbers. All of the agents were diurnal. However, the time of activity was varied. Rainy season gained more flowers and visits, but in contrast, resulted in fewer fruits at all sites. Both flowers abundance and pollination were negatively correlated to the reproductive parameters. Populations might gain more flowers and visits, but the reproductive outputs were significantly lower. Particularly in the clonalized and lower heterozygosity populations, more flowers increased geitonogamy which may lead to inbreeding depression.